NILAI SOSIAL BUDAYA DALAM CERITA RAKYAT SUMATERA SELATAN DAN IMPLIKASINYA DI SEKOLAH - Rahman Mutiara; Amara Revalia; Dodik Hermawan (Jurnal Multidisipliner Bharasa, 2023)
Folklore is basically a reflection of a value that prevails in a particular society. In addition, folklore also describes the characteristic potential of society in different times and times. This paper aims to explore further the socio-cultural value in South Sumatran folklore. In addition, this paper also explores the implications of instilling these social and cultural values in educational institutions. This research began with a literature review of folklore in South Sumatra in terms of Ian Watt's theory of Literary Sociology. The results of this literature review then become the basis for observing the implementation and implications of instilling social and cultural values in SD Negeri 1 Palembang. The results of the study show that folklore in South Sumatra is closely related to the theme of the kingdom. In the view of Social Sociology, folklore in South Sumatra is a reflection of truth and moral values. This moral value contains in it the social and cultural values of a society. Meanwhile, the implementation of instilling social and cultural values through stories at SD Negeri 1 Palembang was carried out on students in grades I and II, using storytelling methods, and providing open questions to learn from each other in understanding social and cultural values. The implications of providing folklore are in line with the fulfillment of learning outputs that give birth to the profile of Pancasila students.